Infrequent SCN9A mutations in congenital insensitivity to pain and erythromelalgia. Issue 4 (5th November 2012) - Klein, Christopher J; Wu, Yanhong; Kilfoyle, Dean H; Sandroni, Paola; Davis, Mark D; Gavrilova, Ralitza H; Low, Phillip A; Dyck, Peter J
Abstract : Objective: Mutations in SCN9A have been reported in (1) congenital insensitivity to pain (CIP); (2) primary erythromelalgia; (3) paroxysmal extreme pain disorder; (4) febrile seizures and recently (5) small fibre sensory neuropathy. We sought to investigate for SCN9A mutations in a clinically well-characterised cohort of patients with CIP and erythromelalgia. Methods: We sequenced all exons of SCN9A in 19 clinically well-studied cases including 6 CIP and 13 erythromelalgia (9 with family history, 10 with small-fibre neuropathy). The identified variants were assessed in dbSNP135, 1K genome, NHLBI-Exome Sequencing Project (5400-exomes) databases, and 768 normal chromosomes. Results: In erythromelalgia case 7, we identified a novel Q10>K mutation. In CIP case 6, we identified a novel, de novo splicing mutation (IVS8-2A>G); this splicing mutation compounded with a nonsense mutation (R523>X) and abolished SCN9A mRNA expression almost completely compared with his unaffected father. In CIP case 5, we found a variant (P610>T) previously considered causal for erythromelalgia, supporting recently raised doubt on its causal nature. We also found a splicing junction variant (IVS24-7delGTTT) in all 19 patients, this splicing variant was previously considered casual for CIP, but IVS24-7delGTTT was in fact the major allele in Caucasian populations. Conclusions: Two novel SCN9A mutations were identified, but frequently polymorphism variants are found which may provide susceptibility factors in pain modulation. CIP and erythromelalgia are defined as genetically heterogeneous, and some SCN9A variants previously considered causal may only be modifying factors.